THE CORRELATION BETWEEN STUDENTS’ METACOGNITION AND THEIR ACADEMIC ACHIEVEMENT IN ENGLISH SUBJECT AT SMAN 8 KENDARI - Amrin, Amrin; Tanduklangi, Amri; Mursalim, Mursalim (Universitas Halu Oleo, 2019)
The study aimed at investigating the correlation between students’ metacognition and their academic achievement at the eleventh grade of SMAN 8 Kendari. The objective of the study is to answer the following research question: is there any significant correlation between student’s metacognition and their academic achievement in English subject at SMAN 8 Kendari?. The study was correlation research study, which employed quantitative research methods. The data was collected from 46 participants who are from SMA N 8 Kendari class XI IPA I and IPS II. The data collection was carried out by using a Metacognition questionnaire and English achievement students from report card. Researcher used cluster random sampling technique in taking the sample. The data of the study was analyzed through Spearman correlation analysis of SPSS 16. The result shows that the coefficient correlation that obtained from the computation is 0,443 and categorized as moderate correlation. The result shows that there is a significant correlation between students’ metacognition and their academic achievement in English subject. This conclusion of this study was drawn through the result of computation which showed that the value of coefficient correlation (r) between two variables, that was students’ metacognition as the variable X and academic achievement as the variable Y, is as moderate as that of the Spearman correlation table with 0,05 level significant. Further, the data showed that there was a moderate correlation. Therefore, it means that the alternative hypothesis was accepted and the null hypothesis was rejected. Keywords: Metacognition, Academic Achievement